Comparative Insecticidal Activity of Artemisia herba-alba Essential Oil from Batna and Khenchela Against Callosobruchus maculatus F in Stored Chickpeas. - Haroun Aicha; Mestour Oumaima (University of Eloued جامعة الوادي, 2025)
This study aims to evaluate the insecticidal efficacy of Artemisia herba-alba essential oil, extracted from two Algerian regions: Batna and Khenchela, against Callosobruchus maculatus F, a major pest that infests stored chickpea seeds. The essential oils were obtained through hydrodistillation and tested using two bioassay methods: direct contact and fumigation. The results revealed strong toxic effects, with high mortality rates recorded after short exposure periods. The essential oil from Batna showed higher effectiveness via direct contact, while the oil from Khenchela was more potent in fumigation tests. These differences are attributed to the variation in chemical composition of the oils due to environmental and climatic conditions in each region. Lethal concentrations (DL10, DL50, DL90) were also calculated using statistical analysis. These findings support the potential of essential oils as eco-friendly and effective alternatives to synthetic insecticides and highlight their role in integrated pest management strategies, particularly in the protection of stored grain products and environmental safety.
Agronomy
Keywords: Artemisia herba-alba; Callosobruchus maculatus F; stored pests; chickpea.